Analysis of The Potential for Utilizing Palm Waste as a Boiler Material in Steam Power Plant PT. Syaukath Sejahtera - Ishak, M. Rizki; Hasannuddin, Teuku (Jurusan Teknik Elektro Politeknik Negeri Lhokseumawe, 2024)
Utilization of palm oil solid waste as boiler fuel is an option in the effort to manage waste in palm oil mills. This utilization is to realize the need for electrical energy for the process of generating electric power by generators. PT. Syaukath Sejahtera is a company engaged in the argo-industrial processing of palm oil into CPO (Crude Palm Oil), has its own power plant system with a total installed electric power capacity of 1000 kW. This research aims to study the potential utilization of palm oil solid waste as boiler fuel at PT. Syaukath Prosperous. After conducting a study by observing field data analysis, it is known that the potential amount of fuel (shells and fibers) is 9450 kg hour and the calculation of the need for boiler fuel is known to be 5149.34 kg/hour. The optimum mixture of waste palm shells and fibers for boilers in PT. Syaukath Sejahtera with a fuel mixture of 25% shells and 75% fiber, namely: Shells 1287.33 kg/hour and fibers 3862 kg/hour with a total steam produced of 20000 kg/hour. The total output of electrical energy from the steam turbine is 706.99 kW, while the electrical energy requirement is 651.14 kW. It can be concluded that the demand for electrical energy in the palm oil processing process at PT. Syaukath Sejahtera has been fulfilled.